Comprehensive Insights into Neuropsychiatric Systemic Lupus Erythematosus - Monika Turek; Klara Wojciechowska; Karolina Piątkowska; Aleksandra Jaroń; Katarzyna Jastrzębska; Iwona Chaberska; Aleksandra Feruś; Julia Lipska (Nicolaus Copernicus University in Toruń, 2024)
Introduction: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease, often affecting women of childbearing age, with periods of exacerbations and remissions. SLE can impact multiple organs, causing a range of clinical symptoms. Neuropsychiatric systemic lupus erythematosus (NPSLE) includes symptoms like headaches, seizures, anxiety disorders, cognitive dysfunctions, psychosis, and neuropathies. Its diagnosis is challenging, and treatment is complex. Purpose: This study aims to explain the pathophysiology of NPSLE, describe diagnostic methods, and summarize current treatment methods based on recent research. Methods: Databases such as PubMed, Medline, and ResearchGate were used. State of current knowledge: Early and accurate diagnosis of SLE is crucial for optimal patient management. The 2019 EULAR/ACR classification criteria have improved diagnostic precision with a weighted scoring system for diverse disease manifestations. Therapy of neuropsychiatric lupus focuses on symptom control and causal treatment, considering anti-inflammatory action or counteracting ischemic incidents. It involves immunosuppressive agents and antiplatelet or anticoagulant substances. Non-pharmacological interventions and lifestyle modifications are also important. The dynamic criteria reflect ongoing advancements in understanding SLE, emphasizing continuous research and collaboration. Conclusions: The diagnosis of NPSLE requires excluding other causes of neuropsychiatric symptoms, such as infections, endocrine disorders, or drug reactions. Diagnostic methods vary based on symptoms, including lumbar puncture, CSF analysis, EEG, cognitive function assessment, and MRI. The treatment of NPSLE focuses on symptom control and causal treatment, with therapy individualized based on symptom severity and patient burden.